Optimal sizing of amenity spaces in a call center facility adopting a multi-phase approach towards a restorative-enhancing office development - Rasonable, Ken F.; Narvaez, Nory Loyd P. (2012)
In today?s competitive global environment, employee productivity is an essential element of a company?s success. Employee productivity can be significantly hindered by high levels of stress experienced in the work environment. In addition, the location and distances of amenities in the office contributes to deterioration of employee health and well-being that can further reduce productivity, especially in the call center environment. The objective of the study is to create a design strategy that would promote a restorative quality of space to the working environment, enhance restoration by increasing staff use and enhancing accessibility by gathering information on the optimal sizing of amenity spaces of select call center facilities of a BPO company in Davao City, and by using this information develop a prototype design that can be applied in a multi-phase development of a Call Center IT Building Complex. The design paradigm was both qualitative and quantitative, and the research method used was a case study. The design solution includes macro and micro-scale elements that increase collaboration and enable teamwork among employees, and a phased strategy that can adapt as a company grows through time, as a means to enhance productivity.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2012